Rice - Technology and Production 2017
DOI: 10.5772/66311
|View full text |Cite
|
Sign up to set email alerts
|

Soil Stabilization with Rice Husk Ash

Abstract: Rice husk ash (RHA) is a by-product of rice milling. Its use as a soil stabilizer is an alternative to the final disposition with environmental benefit. Because RHA is not self-cementitious, a hydraulic binder such a lime must be added to form cements to improve the soil strength. Researches on stabilization by applying RHA and lime combinations were conducted in sandy soils. RHA of no-controlled rice husk incineration in conventional ovens and of laboratory burning at controlled temperatures were used. The al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 15 publications
0
22
0
2
Order By: Relevance
“…A lot of research on stabilizing lateritic soil using RHA has been reported in the literature [13, 14, and 15] and more is needed, especially, in mixing RHA with the conventional binders such as cement in which the influence of RHA on some soils with improvement in their engineering properties can be studied. The use of other locally produced additives including RHA, in the stabilization of lateritic and other soil types, has also been reported [16]. Table 1 shows the chemical composition of RHA as reported in the literature as discussed above [17].…”
Section: Rice Husk Ashmentioning
confidence: 99%
“…A lot of research on stabilizing lateritic soil using RHA has been reported in the literature [13, 14, and 15] and more is needed, especially, in mixing RHA with the conventional binders such as cement in which the influence of RHA on some soils with improvement in their engineering properties can be studied. The use of other locally produced additives including RHA, in the stabilization of lateritic and other soil types, has also been reported [16]. Table 1 shows the chemical composition of RHA as reported in the literature as discussed above [17].…”
Section: Rice Husk Ashmentioning
confidence: 99%
“…In terms of compressive strength improvement, the optimum dosage for some siliceous binder types (15 to 28% for RHA [54,77]) differ from aluminosilicate binders (5 to 10% replacement dosage for GGBS [48] and MK [56,57,86]). A comprehensive comparison of optimum dosage between the two groups of pozzolans when combined with cementitious binder for different soil types e.g.…”
Section: Discussionmentioning
confidence: 99%
“…High-temperature combustion produces more crystalline forms of SiO2 as opposed to the low temperature combustion process. This can be differentiated through colourhigh temperature ash (>900 P o P C) produces fully crystalline silica and is white / pink in colour whereas lower temperature ash (500-700 P o P C) is darker (grey to black) with more amorphous silica that is more reactive [75]. This is counteracted by less SiO2 derived from lower furnace temperature furnaces vs higher furnace temperature.…”
Section: Rice Husk Ash (Rha)mentioning
confidence: 99%
“…Pozzolanas are siliceous and/or aluminous materials, which in themselves possess minute or no cementing properties, but chemically react with calcium hydroxide, such as lime, to form compounds possessing cementitious properties. The rice husk ash contains around 90% of silica which is the maximum concentration of all plant residues [12]. A work is undertaken to study on engineering properties of black cotton soil which is stabilized using rice husk ash (RHA) and lime with randomly distributed polypropylene fiber (PPF).…”
Section: Rice Husk Ash and Limementioning
confidence: 99%